"The sun keeps rising but darkness surrounds us": a qualitative exploration of the lived experiences of women with obstetric fistula in Ethiopia - Misganaw Animut; Abebe Mamo; Lakew Abebe; Million Abera Berhe; Shifera Asfaw; Zewdie Birhanu (BMC, 2019)
Abstract Background Obstetric fistula is a hole between the vagina and bladder, and/or between the vagina and rectum, triggered by prolonged obstructed labor. The World Health Organization has estimated that at least 50,000 to 100,000 cases of obstetric fistula occur every year, and that over two million women with obstetric fistula in developing countries remain untreated. Research on women's lived experiences of obstetric fistula is limited. This study aimed to explore the lived experience of women with obstetric fistula at Bahir Dar Hamlin Fistula Center, Amhara Regional State, Ethiopia. Methods A qualitative study design, drawing from a phenomenological approach, was employed to explore the lived experience of purposively-selected sample of ten women with obstetric fistula. In-depth interviews were conducted in the local language (Amharic) using an interview guide. Interviews were transcribed and translated into English, and transcripts were entered as primary documents into Atlas.ti 7 software. Thematic categories were identified, and transcripts were coded accordingly. Results Participants perceived that the contributing factors to obstetric fistula were: instrument-assisted delivery; inappropriate physical examination and care; early marriage; and long duration of labour. As a result of obstetric fistula, the patients suffered from uncontrolled dripping of urine and/or faeces (and associated offensive odours), ostracization by their family and community members, and feeling hopeless and isolation from the community. Patients used different coping mechanisms, including frequent washing of clothes and changing of underwear; they also expressed that they preferred to be alone. Conclusion Women with obstetric fistula experienced urine incontinence and associated bad odour; social and psychological problems like isolation, divorce and fears were commonly reported. Our findings from perspectives of Ethiopian setting suggest that integrated services for women with obstetric fistula are warranted, including physical therapy, psychological support and social reintegration.